VITAL phase 2 study: Upfront 5‐fluorouracil, mitomycin‐C, panitumumab and radiotherapy treatment in nonmetastatic squamous cell carcinomas of the anal canal (GEMCAD 09‐02). (18th December 2019) - Feliu, Jaime; Garcia‐Carbonero, Rocio; Capdevila, Jaume; Guasch, Inmaculada; Alonso‐Orduna, Vicente; Lopez, Carlos; Garcia‐Alfonso, Pilar; Castanon, Carmen; Sevilla, Isabel; Cerezo, Laura; Conill, Carles; Quintana‐Angel, Begona; et al.
Abstract: Aim: VITAL, a phase II single‐arm study, aimed to evaluate efficacy and safety of panitumumab addition to 5‐fluorouracil (5‐FU), mitomycin‐C (MMC) and radiotherapy (RT) in patients with localized squamous cell carcinoma of the anal canal (SCCAC). Methods: Adult, treatment‐naïve SCCAC patients (Stage T2‐T4, any N, M0) and ECOG‐PS ≤2, received panitumumab (6 mg/kg, day 1 and Q2W; 8 weeks), 5‐FU (1000 mg/m 2 /d, days 1‐4 and 29‐32), MMC (10 mg/m 2, days 1 and 29) and RT 45 Gy (1.8 Gy/fraction) to the primary tumor and mesorectal, iliac and inguinal lymph nodes, plus 10‐15 Gy boost dose to the primary tumor and affected lymph nodes. The primary objective was disease free survival rate (DFS) at 3‐years (expected 3‐year DFS rate: 73.7 ± 12%). Results: Fifty‐eight patients (31 women; median age: 59 years; ECOG‐PS 0‐1:98%; TNM II [29%] (T2 or T3/N0/M0)/IIIA (T1‐T3/N1/M0 or T4/N0/M0) [21%]/IIIB (T4/N1/M0 or any T/N2 or N3/M0) [47%]/nonevaluable [4%]) were included. The median follow‐up was 45 months. The 3‐year DFS rate was 61.1% (95% CI: 47.1, 72.4). The 3‐year overall survival rate was 78.4% (95% CI: 65.1, 87.1). Eighteen patients (31.0%) required a colostomy within 2 years posttreatment. Grade 3‐4 toxicities were experienced by 53 (91%) patients. Most common grade 3‐4 treatment‐related events were radiation skin injury (40%) and neutropenia (24%). No toxic deaths occurred. Improved efficacy in colostomy‐free survival and complete response rate was observed in human papilloma virus positive patients. Conclusions: Panitumumab addition to MMC‐5FU regimen in SCCAC patients increases toxicity and does not improve patients' outcomes. RT plus MMC‐5FU remains the standard of care for localized SCCAC patients. Abstract : VITAL, a phase II single‐arm study, was aimed to evaluate efficacy and safety of panitumumab addition to 5‐fluorouracil (5‐FU), mitomycin‐C (MMC) and radiotherapy in patients with localized squamous cell carcinoma of the anal canal (SCCAC). The study concluded that panitumumab addition to MMC‐5FU regimen in SCCAC patients increases toxicity and does not improve patients' outcomes.